Comunicação quântica baseada no teletransporte em variáveis contínuas - Luiz, Fabrício de Souza (Universidade Federal de São Carlos, 2014)
In this Thesis we study in details one of the most astonishing application of quantum mechanics which totally departs from our common sense: quantum teleportation in continuous variables. We present a review of the postulates of quantum mechanics and quantum optics systems, in particular for Gaussian systems. After this review we apply these postulates in order to present one of the most counter intuitive applications of quantum mechanics, namely, the quantum teleportation protocol. We study in detail this protocol and we propose modifications in its construction aiming at an improvement in its efficiency. These modifications were made in order to take into account the realistic situations encountered in the implementation of the protocol, i.e., the fact that the entanglement, between Alice and Bob, is never perfect and the fact that states teleported by Alice are near the vacuum state. After this analysis we performed an extension of the teleportation protocol by proposing a multi-channel protocol and studied the case of two channels in parallel. Finally, we created the first quantum cryptography protocol that uses the continuous variables teleportation protocol in an active way. We showed that this protocol is robust to the beam splitter attack and that this protocol is the only one working with direct reconciliation and without post-selection over the 50% loss scenario.
Keywords: Física quântica; Teletransporte; Variáveis contínuas; Canal; CIENCIAS EXATAS E DA TERRA::FISICA